Clinical and individual features associated with maternal stress in young adolescents with autism spectrum disorder. Issue 9 (20th May 2021) - Scibelli, Francesco; Fucà, Elisa; Guerrera, Silvia; Lupi, Elisabetta; Alfieri, Paolo; Valeri, Giovanni; Vicari, Stefano
Abstract: Parents of people with autism spectrum disorder experience both negative stressful and positive events. Several clinical and socio‐demographic features of children on the autism spectrum have been associated with parenting stress in their families. However, there have been few studies that focus on adolescents and the role of cognitive impairment has rarely been addressed. The main aim of the present research is to explore associations between autism symptoms, cognitive impairment, emotional and behavioral problems, socio‐demographic features, and maternal stress in a sample of young adolescents with Autism Spectrum Disorder with and without cognitive impairment. Cognitive impairment and emotional and behavioral problems are associated with maternal stress, while autism symptoms seem to play a minor role. Maternal education and occupation are only associated with maternal stress in the group with cognitive impairment, while maternal age is stress‐associated in the group of adolescents without cognitive impairment. Age‐related implications for intervention and future research directions are discussed. Lay Summary: Parents of individuals on the autism spectrum are exposed to both negative stressful and enriching experiences during their parenthood. While the influence of several child characteristics and socio‐demographic features on parental stress during childhood has been widely explored in past studies, studies on teenagers are limited. The aim of the present research is to explore the influence of several characteristics on maternal stress levels in families with teenagers on the autism spectrum. We found that cognitive impairment and emotional and behavioral problems are associated with maternal stress, while autism symptoms seem to play a minor role. Socio‐demographic features are not associated with maternal stress. Broadly speaking, the subjective perception of parental distress in both groups is less related to teenagers' characteristics then the perception of having a difficult interaction with the teenagers. We divided our participants into two groups (one group with cognitive impairment and the other group without). We found that mothers of teenagers with cognitive impairment are generally more stressed compared to the other group. Furthermore, we confirm that emotional and behavioral problems seem to play a major role in maternal stress (especially in the group without cognitive impairment), while autism symptoms seem to play a minor role. Furthermore, we found that maternal education/occupation and maternal age are associated with maternal stress in the group with and the group without cognitive impairment respectively. This research highlights the association between several variables and stress in mothers of adolescents on the spectrum. Results are discussed in the framework of previous findings highlighting the lack of adequate care and support services for families, especially for those of adolescents on the spectrum with cognitive impairment.